Preparation and Characterization of Potential Zeolite Based Ruthenium Catalysts - Prasad Banerjee, Sati (Asian Journal of Chemistry, 2012)
Mineral acid treatment and interaction with a chelating agent of a Ru(III)-13X zeolite brings about dealumination to the extent of 56.8 % and decationisation to the extent of 44.9 % in the original zeolite before calcinations. After calcinations further dealumination occurs for a total extent of 67.0 % and decationisation remains almost unchanged (45.8 %). The interacted sample before calcinations shows the presence of complex ruthenium species. This sample and its calcined form have been characterized by TG, FT-IR and SEM studied and determination of N % and both exhibit thermal stability and minor changes in the crystal structure.